Diffuse large B-cell and follicular lymphoma presenting as a slowly growing compressive goiter: A case report and literature review. (2020) - Lin, Nicole; Vargas-Pinto, Susana; Gisriel, Savanah; Xu, Mina; Gibson, Courtney E.
Highlights: Rapid, but not slowly growing goiters are generally concerning for malignancy. Lymphoma represents < 5% of all primary thyroid malignancies. Hashimoto's thyroiditis is a known risk factor for thyroid lymphoma. Core needle biopsy is highly sensitive for diagnosis of thyroid lymphoma. Multimodal treatment of thyroid lymphoma is preferred. Abstract: Introduction: Neck ultrasonography with fine-needle aspiration cytology (FNAC) is the diagnostic modality of choice for clinicians who routinely work up a thyroid mass. Distinguishing chronic lymphocytic infiltration from a lymphoproliferative process with FNAC in patients with Hashimoto's thyroiditis presenting with a goiter can be particularly challenging. Case description: A 58 y.o. female with a history of a goiter showing interval growth and compressive symptoms over 18 months, was treated with a thyroid lobectomy. Surgical pathology demonstrated a thyroid lymphoma (TL) with mixed follicular and diffuse large B cell (DLBCL) components, not initially diagnosed by FNAC. Staging workup showed the involvement of chest lymph nodes only, consistent with Stage IIE disease. She was treated with combination chemotherapy and immunotherapy, followed by involved-field radiotherapy. Discussion: TL often arises in a background of chronic lymphocytic thyroiditis which can make its histological diagnosis a challenge. The disease is heterogeneous in histological subtype and progression. Conclusion: While TL usually presents as a rapidly growing neck mass, indolent types can present as a slow growing mass with subsequent transformation. Patients may benefit from avoiding unnecessary diagnostic steps, including surgery, and potential delays in treatment by performing a core needle biopsy when a lymphoproliferative process cannot be excluded if FNAC was initially performed.